2003
DOI: 10.1067/mcp.2003.26
|View full text |Cite
|
Sign up to set email alerts
|

Itraconazole increases but grapefruit juice greatly decreases plasma concentrations of celiprolol

Abstract: Itraconazole almost doubles but grapefruit juice greatly reduces plasma concentrations of celiprolol. The itraconazole-celiprolol interaction most likely resulted from increased absorption of celiprolol possibly as a result of P-glycoprotein inhibition in the intestine. The reduced celiprolol concentrations during the grapefruit juice phase were probably caused by physicochemical factors that interfered with celiprolol absorption, although other mechanisms cannot be excluded. The grapefruit juice-celiprolol in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
120
1
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(129 citation statements)
references
References 30 publications
(56 reference statements)
6
120
1
2
Order By: Relevance
“…Levothyroxine is susceptible to complexation with other drugs in the gastrointestinal tract [10,11], and grapefruit juice is characterized by its acidity [7]. Thus, grapefruit juice components appear to have only a minor potential to interfere with the absorption of levothyroxine from the intestinal lumen either by binding to the drug or by increasing the acidity of the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Levothyroxine is susceptible to complexation with other drugs in the gastrointestinal tract [10,11], and grapefruit juice is characterized by its acidity [7]. Thus, grapefruit juice components appear to have only a minor potential to interfere with the absorption of levothyroxine from the intestinal lumen either by binding to the drug or by increasing the acidity of the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that grapefruit juice markedly decreases plasma concentrations of fexofenadine and celiprolol [6,7]. It has been suggested that the mechanism of the grapefruit juice-fexofenadine interaction is inhibition of uptake transporters in the intestinal wall that results in decreased absorption [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OATP influences the intestinal absorption of several drugs in clinical use. [10][11][12][13][14] Grapefruit juice decreases the plasma concentrations of some drugs including β-adrenoceptor blocking agents and antihistamines by this mechanism. For example, grapefruit juice was reported to reduce the area under the plasma concentration-time curve (AUC) value for fexofenadine to a mean value of 58% of that when the drug was administered with the corresponding volume of water.…”
Section: )mentioning
confidence: 99%
“…Thus, our goal was to determine the duration of the inhibitory effect of grapefruit juice on OATP by comparison with the duration of the grapefruit juice-mediated effects on CYP3A4 activity. We administered oral celiprolol and midazolam, which are substrates of OATP 3,11) and CYP3A4, 1,14) respectively, on days 1, 3, and 7 (0, 48, and 144 h after the ingestion of grapefruit juice) to healthy subjects. …”
mentioning
confidence: 99%